THE ROLE OF ORGANIZATIONAL JUSTICE, ORGANIZATIONAL SUPPORT AND ORGANIZATIONAL COMMITMENT TOWARDS IMPROVING EMPLOYEE PERFORMANCE AT CV BINA FURNITURE PEKANBARU - Raden Rudi Alhempi; Budi Alamsyah Siregar; Lili Salfina; Muhammad Hendra; Raja Marwan Indra Saputra; Dorris Yadewani; Ropella Naibaho (Jurnal Apresiasi Ekonomi, 2026)
Employee performance has become an essential indicator of organizational success, particularly in competitive industries such as the furniture sector, where productivity, quality of work, and responsibility strongly determine business sustainability. The importance of understanding factors that shape employee performance is increasingly relevant because many small and medium-sized enterprises face challenges related to fairness, limited organizational support, and fluctuating employee commitment. This study aims to analyze the influence of organizational justice, organizational support, and organizational commitment on employee performance at CV Bina Furniture Pekanbaru. Using a quantitative approach supported by structural equation modeling, the study evaluates how perceptions of fairness, support from management, and the psychological attachment of employees interact in shaping performance outcomes. The findings reveal that organizational justice positively contributes to improving employee performance and strengthens employee commitment. Organizational support also demonstrates a significant role in enhancing performance as well as reinforcing employee commitment toward the organization. Furthermore, organizational commitment is proven to be a strong predictor of employee performance, indicating that employees with higher emotional attachment tend to show better work outcomes. These results highlight the need for managerial policies that ensure fairness, provide adequate support, and foster commitment to optimize performance in small and medium-scale enterprises.